Study of the Electronic Properties and Hall Effect of Amorphous Si1-xGex:H Thin Films - Alias, M. F.A. (Iraqi Journal of Physics, 2009)
The electronic properties and Hall effect of thin amorphous Si1-xGex:H films of thickness (350 nm) have been studied such as dc conductivity, activation energy, Hall coefficient under magnetic field (0.257 Tesla) for measuring carrier density of electrons and holes and Hall mobility as a function of germanium content (x = 0–1), deposition temperature (303-503) K and dopant concentration for Al and As in the range (0-3.5)%. The composition of the alloys and films were determined by using energy dispersive spectroscopy (EDS) and X-ray photoelectron spectroscopy (XPS). This study showed that dc conductivity of a-Si1-xGex:H thin films is found to increase with increasing Ge content and dopant concentration, whereas conductivity activation energy decreases with increasing Ge content and dopant concentration. The carrier density (electrons and holes) of prepared films increases with increasing Ge content, dopant concentration and deposition temperature. The mobility and the mobility activation energy increase with increasing Ge content. The width of localized state is 0.215 eV for a- Si0.5Ge0.5:H thin film deposited at 503 K.